RELATIONSHIP BETWEEN PRICE WITH PATIENT SATISFACTION IN HOSPITAL BHAKTI MEDICARE, CICURUG, REGENCY OF SUKABUMI (Lembaga Penelitian dan Pengabdian Nasyarakat Universitas Pakuan, 2018)
The purpose of this study is to determine the presence or absence of prince relationships with patient satisfaction in hospitals Bhakti Medicare, Cicurug, Sukabumi. The population of this research are Bhakti Medicare hospital patient, Cicurug, Sukabumi consisting of jasmine room patient, rose room, dahlia room and orchid room with a population of 130 patiens where to get the minimum sample amount used slovin’s formula. After the calculation obtained by the sample of 100 repondents. The collected data is then processed using simple correlation and multiple correlation techniques using SPSS (statistical Package for social science) software. Result of research : There is positive relation between price with correlation coefficient value equal to (ry.1) = 0.679 included in strong relationship category. While Price contribution to patient satisfaction equal to r2 = (ry.1)2 = 46,2%. The results of the international study provide some implications with the results of the hypothesis obtained include: proce contribution is considered strong against patient satisfaction which means increased price will ensure patient satisfaction in Bhati Medicare hospital, Cicurig, Sukabumi regency. The results of the international study provide that price hace trong relation with costomer satisfaction equal to (r) = 0.348 units. In the most important dimension proce variable the relationship is the dimension of “patment period” (X14) which has the strongest relationship with “consistency” dimension (Y3) on patient satisfaction variable with correlation coefficient 0,641 (strong relation). Thus it can be concluded that the price dimension that most determine patient satisfaction at Bhakti Medicare Hospotal, Cicurug, Sukabumi Regency is the dimension of price. Keywords: price, patient satisfaction and payment period